The potential of graphene nanoplatelets in the development of smart and multifunctional ecocomposites - Pereira, Pedro (2020)
Graphene and its derivatives have shown outstanding potential in many fields and textile/composites industry are not an exception. Giving their extraordinary properties, Graphene Nanoplatelets (GNPs) are excellent candidates for providing new functionalities to fibers and composites. In this work, natural fabrics (flax) were functionalized with chitosan (CS) based polymeric formulations of GNPs to develop fibrous systems with electrical properties as well as other functionalities. One of the greatest disadvantages of using carbon-based materials for fabrics’ impregnation is their difficult dispersion. Therefore, several polymers were used as matrices, binding and dispersive agents including chitosan, polyethylene glycol (PEG), and glycerol. All the systems were characterized using several techniques that demonstrated the presence and incorporation of the GNPs onto the composites. Besides their characterization, considering their use as smart materials for monitoring and sensing applications, electrical properties were also evaluated. The highest value obtained for electrical conductivity was 0.04 S m−1 using 2% of GNPs. Furthermore, piezoresistive behavior was observed with Gauge Factor (GF) of 1.89 using 0.5% GNPs. Additionally, UV (ultraviolet) protection ability and hydrophobicity were analyzed, confirming the multifunctional behavior of the developed systems extending their potential of application in several areas.